(untitled) (Dhaka University Journal of Biological Sciences, 2014)
The reproductive biology of the flesh fly, Boettcherisca peregrina (Diptera : Sarcophagidae ) was studied in the blowfly laboratory (25 -30ºC, 60 - 80% RH and 12 hrs light and 12 hrs dark) of the Institute of Food and Radiation Biology, Atomic Energy Research Establishment, Dhaka. The female reproductive system of B. peregrina comprises of two ovaries, two lateral oviducts, a common oviduct, three spermathecae, and a pair of accessory gland, a bilobed incubation pouch, vagina and genital opening. The male reproductive system B. peregrina consists of a pair of testes, a pair of vasa deferentia, a pair of accessory gland, a median ejaculatory duct, an ejaculatory sac and aedeagus. There is a general trend of gradual development of different organelles of the male and female reproductive systems from adult emergence to reproductive maturity. Protein diet was essential for proper development of female reproductive system. Oocyte development was apparent in both protein fed and protein unfed females. The mean sex-ratio of male to female was 20.2 : 14.2.